2018
DOI: 10.1016/j.ultsonch.2017.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of chitosan nanoparticles from shrimp shells and investigation of its catalytic effect in diastereoselective synthesis of dihydropyrroles

Abstract: Preparation of chitosan nanoparticles (CS-NPs) was examined from shrimp shells for their catalytic activity. The yield of crude chitosan was 87.8%. The structure of chitosan nanoparticles was determined by FT-IR, SEM and XRD analysis. Then, diastereoselective synthesis of dihydropyrroles was done using chitosan nanoparticles in water under ultrasonic irradiation. This polymeric nanocatalyst could be used instead of the old toxic commercial organic basic catalysts and could be readily isolated from the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…Thus, XRD showed that AgNPs were produced by the reduction of AgNO 3 with shrimp extract (Figure 4), where crystal structure well matched with earlier reports [15,51,57]. Furthermore, the crystalline nature of shrimp-derived chitosan nanoparticles was determined by the most intense diffraction peaks at values of 11.7 and 20.2° [58]. FTIR studies were conducted to reveal the probable chemicals contributing to the reduction of silver nanoparticles ( Figure 5).…”
Section: Results and Discussion 31 Characterisation Of Cs-agnpssupporting
confidence: 80%
“…Thus, XRD showed that AgNPs were produced by the reduction of AgNO 3 with shrimp extract (Figure 4), where crystal structure well matched with earlier reports [15,51,57]. Furthermore, the crystalline nature of shrimp-derived chitosan nanoparticles was determined by the most intense diffraction peaks at values of 11.7 and 20.2° [58]. FTIR studies were conducted to reveal the probable chemicals contributing to the reduction of silver nanoparticles ( Figure 5).…”
Section: Results and Discussion 31 Characterisation Of Cs-agnpssupporting
confidence: 80%
“…This component is the primary precursor of chitosan. Partial deacetylation of chitin was developed to obtain the product using sodium hydroxide [ 53 ].…”
Section: Case Study: Chitosan Production From Shrimp Exoskeletonmentioning
confidence: 99%
“…The facility of accomplishment multicomponent reactions with a recyclable catalyst under ultrasonic irradiation could advance the efficiency of organic reactions. [18] The ultrasonic energy shortens the reaction time and enhances the reaction rate. [19][20][21][22] Metal oxides have been widely utilized in diverse fields.…”
Section: Introductionmentioning
confidence: 99%